Characterization of Phaseolus coccineus interspecific germplasm accessions for disease resistance, grain market class and yield attributes - Mukankusi, Clare Mugisha; Amongi, Winnyfred; Sebuliba, Sulaiman; Musoke, Stephen; Acam, Catherine (African Journals Online, 2018)
Sister species of the common bean (Phaseolus vulgaris L.) are an attractive genetic resource to broaden the genetic base of this crop, especially for adaptation to extreme environments. The runner bean (Phaseolus coccineus) in particular, has been shown to contribute to disease resistance and tolerance to low soil fertility, and has been used to introduce these traits into the common bean. The objective of this study was to identify germplasm with agronomic traits suitable for cultivation from an interspecific population (Phaseolus coccineus G35346 x P. vulgaris; SER 16) of 186 bush lines. The lines, coded ALB and one yield check, CAL96, were field evaluated for three rain seasons; 2011a (March-June), 2011b (September-November) and 2012 (March-June) at the National Agricultural Research Laboratories (NARL)-Kawanda, Uganda. Artificial inoculum of bean common mosaic virus (BCMV) was applied to the field experiment in 2011a. The morphological (seed type and growth habit) and agronomic attributes (plant vigour, days to physiological maturity; DPM and days to 50% flowering; DF), reaction to occurring diseases and yield performance were monitored. The lines including root rot resistant and susceptible checks; MLB-49-89A, RWR 719 and CAL 96, were also subjected to inoculum of two major root rot pathogens; Fusarium solani f.sp. phaseoli (isolate FSP3) and Pythium ultimum (isolate MS61) under screen house conditions to select for root rot resistance. Results indicated significant differences (P<0.05) among the interspecific lines for the parameters measured. Days to flowering and to DPM ranged from 31-39 and 81-86, respectively. Field disease pressure was generally low, but in general, 50% of the lines had yield above the mean; while 8% maintained above average yield in all seasons. The superior lines included; ALB169 (mean yield 2,564 kg ha-1), ALB214 (mean yield 2,125 kg ha-1), ALB196 (mean yield 2,084 kg ha-1), ALB5 (2,062 kg ha-1), ALB152 (2,016 kg ha-1), and ALB179 (2011 kg ha-1), compared to the check CAL96 (1,607 kg ha-1). These lines, except ALB169 and ALB179, were resistant root rot. More lines expressed resistance to Fusarium than to Pythium root rot, with 21.5% showing resistance to both root rot isolates. Over 91% of the lines were small or medium seeded (< 35.0 g per 100 seeds), with red monochrome seed pattern; characteristics that are important for farmer acceptance.